The Person: Vital Core of the Pedagogic Mediation Process - Miranda Cervantes, Giselle (2013)
The main purpose of this paper is to place the person as the basic element in education and, particularly, in the pedagogic mediation process. Based on her own personal and professional experiences, and inspired by writers such as Gutiérrez, Krishnamurti, Maturana, Morin and Prieto, the author uses the terms student-person and teacher-person as a way of truly re-discovering and re-learning that vital element immersed in a magical relational space, where the human being is strengthened as an individual and as part of a planetary family.  Most of all, the author gives the deserved emphasis to the bond constructed from a true intertwining emotional flow.  Academic insides are accompanied by experiences based on the use of the Parallel Text as a pedagogic mediation